Home range size and habitat use of the blue-crowned laughingthrush during the breeding season - Tao Liu; Yongtao Xu; Bai Mo; Jinze Shi; Yachang Cheng; Weiwei Zhang; Fumin Lei (PeerJ, 2020)
The home range size and habitat use of the blue-crowned laughingthrush (Garrulax courtoisi, hereafter BCLT), a critically endangered, subtropical, cooperative-breeding bird species in southeast China, were studied during its breeding period using radio telemetry at different sites during 3 consecutive years (2016–18, from May to June of each year). A total of 17 birds (12 males, four females, and one of unknown sex) were tagged, and a total 1515 locations (mean ± se = 89.12 ± 11.42) were obtained over 54 days of tracking. The average 100% minimum convex polygon (MCP) home range size was 10.05 ± 1.17 ha, and the estimated KDE core area (fiexed kernel density estimator, KDE) size was 7.84 ± 1.18 ha. According to the Wilcoxon rank sum tests, both the 100% MCP and KDE core area size of males did not significantly differ from those of females. There were no significant differences in the 100% MCP or KDE core area sizes of the three breeding sites. The available habitats in the breeding sites included water areas, shrubs, grass plots, woodland, residential areas, vegetable field, farmland, and sandy beaches; among them, only woodland was significantly preferred by BCLTs. Woodland (average use ratio was 45.86 ± 1.74%) was strongly preferred by BCLTs for nesting, foraging and roosting. Shrubs/grass plots (24.72 ± 3.39%) and vegetable plots (11.80 ± 1.83%) were used relatively more often than the other habitats, except woodland, since shrubs were always used as perches, and vegetable plots were rich in food resources. Vertically, the canopy layer was used most often from April to June, but it was used most in May when the birds were hatching and brooding. This result indicates that BCLT is predominantly active in the upper strata during the breeding season. In addition, broadleaved trees within or adjacent to villages were important activity areas for the breeding birds; protection and management measures should be increased in these areas.